Ten Years After SINS: Role of Surgery and Radiotherapy in the Management of Patients With Vertebral Metastases - Serratrice, Nicolas; Faddoul, Joe; Tarabay, Bilal; Attieh, Christian; Chalah, Moussa A.; Ayache, Samar S.; Abi Lahoud, Georges N. (Frontiers in Oncology, 2022)
Background: The spine is the most common site of skeletal metastases. Since its appearance in 2010, the Spine Instability Neoplastic Score (SINS) has quickly found its place in the decision tree for the management of vertebral metastases, either by surgery or conservative oncological therapy (radiation therapy and/or chemotherapy). Methods: Here we offer a review of the literature describing the changes that have occurred in our practice and in the management of patients with spinal metastases in the last ten years. Review: After a brief presentation of the spinal metastases’ distribution, with or without spinal cord compression, we present the utility of SINS in the radiological diagnosis and extension of the diseases. Impact of SINS in the oncological spinal therapy will also be discussed with a special attention to scores ranging between 7 and 12. We expose the latest advances in surgery and radiotherapy concerning spinal metastases, as well as in palliative care and pain control. We also discuss the reliability of SINS amongst radiologists, radiation oncologists, spine surgeons and spine surgery trainees. Finally, we will present the new SINS-derived predictive scores, biomarkers and artificial intelligence algorithms for the management of spinal metastases. Conclusion: The goal of any therapeutic course for a spinal metastasis is to provide the best oncological and functional result with the least aggressive treatment. Novel surgical and radiotherapy scores could allow a multidisciplinary approach to the metastatic spine.